Caracterização do sistema agroextrativista familiar do açaizeiro nativo (Euterpe oleracea Mart.), da Comunidade Quilombola São Maurício, Alcântara, Maranhão - Machado, Ricardo Lucas Bastos (2008)
The Açaizeiro (Euterpe oleracea Mart.) is a typical forest species of the Estuary of Amazon. In the Maranhão, the same botanical species occurs, but the fruit popularly is known as juçara. The objective of this work is to characterize the agroextrativista system of açaí practised by small agriculturists in fertile valley area of the Community Is Maurício, Alcântara, MA, from the phytosociology knowledge of the ecosystem, the agronomics petitions of handling and of the study of the partner-economic of the community. For accomplishment of this work 16 parcels of 20 for 20 meters duly identified and demarcated by striped ribbon had been selected. In the phytosociology survey the referring data to the identification in level of popular name, scientific and family, total height and circumference to the height of the chest had been collected in field, classification of the species in relation to the ecological paper that exerts inside of the ecosystem, with emphasis for trees of service and multiple use and analyzing each species the parameters absolute frequency, basal area, relative domain for area, relative density, relative frequency, relative domain, value of importance, value of covering and index of diversity of Shannon and Weaver. Still as characterization of the study area the native production was analyzed, collecting given of number of clusters harvested for plant, total of weight of the fruits, average of weight of the fruits, total of weight of the pulp, average of weight of the pulp, average of income of the pulp in percentage, beyond analyzing soluble solids gifts in the pulp, the titulável total acidity and acidity in pH. The average values of 1,86 º Brix, 0,17 for titulável total acidity and 5,05 for pH, serve of parameter for other harvests that will be carried through in the managemented area already and show that the flesh of açaí studied is within the criteria established by the Ministry of agriculture and supply. Also in this work a partner-economic questionnaire of the community was become fullfilled, where if it detected that although the community to be sufficiently devoid and with low level of school, sufficiently revealed expert of the importance of the “baixa” having açaí as the main source of feeding and income.